Study of cardiac changes in children with malnutrition - Mannu, Alexander; Narayana, Ganesh; Ramagopal, Ganavi; Vasudevan, Jaishree; Nayar, Pradeep G (Indian Journal of Child Health, 2017)
Background: Children with malnutrition usually exhibit several alterations in the body composition, one of them being a loss of cardiac muscle and its consequences. Aim: The aim of this study is to detect the incidence of cardiac involvement among malnourished schoolchildren as shown by clinical examination and corresponding investigations. Methodology: This is a prospective case-control study conducted on 15 children between 5 and 15 years of age with malnutrition. Inclusion criteria were children who fall under the definition of moderate malnutrition as per the World Health Organization (WHO) Z-score based on the WHO Child Growth Standards. Children with known congenital/acquired heart diseases were excluded from the study. Thesechildren were assessed by echocardiography and estimation of cardiac troponin T (cTn T) levels for cardiac involvement that was compared with 12 healthy controls. Results: The mean left ventricular mass (LVM) was 16.74 units higher in children with normal nutritional status compared with malnourished children (p=0.092, 95% confidence interval=2.91-36.40).The mean LVM index was 4.76 units higher in children with normal nutritional status compared with kids with malnutrition indicating the reduction of cardiac muscle mass. Conclusion: As cardiac muscle mass is reduced in children with malnutrition leading to various complications, they need early detection, monitoring, and appropriate management.